Liver Stiffness Assessed by Ultrasound Shear Wave Elastography from General Electric Accurately Predicts Clinically Significant Portal Hypertension in Patients with Advanced Chronic Liver Disease - Stefanescu, Horia; Rusu, Corina; Lupsor-Platon, Monica; Nicoara Farcau, Oana; Fischer, Petra; Grigoras, Crina; Horhat, Adelina; Stancu, Oana; Ardelean, Andreea; Tantau, Marcel; Badea, Radu; Procopet, Bogdan (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose Clinically significant portal hypertension (CSPH) is responsible for most of the complications in patients with cirrhosis. Liver stiffness (LS) measurement by vibration-controlled transient elastography (VCTE) is currently used to evaluate CSPH. Bi-dimensional shear wave elastography from General Electric (2D-SWE.GE) has not yet been validated for the diagnosis of PHT. Our aims were to test whether 2D-SWE.GE-LS is able to evaluate CSPH, to determine the reliability criteria of the method and to compare its accuracy with that of VCTE-LS in this clinical setting.Materials and Methods Patients with chronic liver disease referred to hepatic catheterization (HVPG) were consecutively enrolled. HVPG and LS by both VCTE and 2D-SWE.GE were performed on the same day. The diagnostic performance of each LS method was compared against HVPG and between each other.Results 2D-SWE.GE-LS was possible in 123/127 (96.90 %) patients. The ability to record at least 5 LS measurements by 2D-SWE.GE and IQR < 30 % were the only features associated with reliable results. 2D-SWE.GE-LS was highly correlated with HVPG (r = 0.704; p < 0.0001), especially if HVPG < 10 mmHg and was significantly higher in patients with CSPH (15.52 vs. 8.14 kPa; p < 0.0001). For a cut-off value of 11.3 kPa, the AUROC of 2D-SWE.GE-LS to detect CSPH was 0.91, which was not inferior to VCTE-LS (0.92; p = 0.79). The diagnostic accuracy of LS by 2D-SWE.GE-LS to detect CSPH was similar with the one of VCTE-LS (83.74 % vs. 85.37 %; p = 0.238). The diagnostic accuracy was not enhanced by using different cut-off values which enhanced the sensitivity or the specificity. However, in the subgroup of compensated patients with alcoholic liver disease, 2D-SWE.GE-LS classified CSPH better than VCTE-LS (93.33 % vs. 85.71 %, p = 0.039).Conclusion 2D-SWE.GE-LS has good accuracy, not inferior to VCTE-LS, for the diagnosis of CSPH.
Keywords: liver stiffness; ultrasound elastography; portal hypertension; noninvasive